FIGURATIVE LANGUAGE OF MILK AND HONEY POETRY COLLECTIONS - Felisha Firstania Putri Grandi; Putu Weddha Savitri; Ni Luh Sutjiati Beratha (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study aimed to identify the types of figurative language and the use of figurative language to deliver the stages of grief applied in the Milk and Honey poetry collections due to its powerful deliverance by using figurative language inside the poetry which made the exploration of the pain of experiencing unpleasant events in an individual’s life more sophisticated. The data were collected by using documentation methods and note-taking techniques. This undergraduate thesis is aimed to discover the types of figurative language and stages of grief found inside the Milk and Honey poetry collections. The data were analyzed by using descriptive and qualitative method. In addition, the theory of Kennedy (1979) was applied in this study. The analysis of this study shows that seven out of eight types of figurative language are found in the poetry collections. They are metaphor, simile, personification, hyperbole, metonymy, symbol and irony. Furthermore, to identify the use of figurative language to deliver the stages of grief, the theory of Ross (1969) was used to enhance the study. There are five stages of grief proposed by the theory, and all of the stages of grief are found in this study. There are denial, anger, bargaining, depression, and acceptance.